Students Age at which EFL is Introduced in Schools and Educational Outcomes - Chuzaimah Dahlan Diem (Universitas Negeri Malang, 2016)
To see the relationship between the age at which EFL is introduced in some Indonesian public schools and student outcomes a survey involving 229 students both from elementary and junior high schools in Palembang is conducted. These students are given the test comprising vocabulary, reading comprehension, and grammar. It is hypothesized that those who start learning English earlier have better achievement. Factors such as school and home environments are also considered in the analysis. Stepwise regression analysis is applied to identify which variable contributes to students outcomes. The results show that there is no correlation between age alone and the students EFL achievement. However, significant influence is found when teacher education level and teacher ELT experience are added to the prediction model predicting EFL achievement from age.